2013
DOI: 10.1155/2013/893479
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Magnetic Mesoporous Bioactive Glass/Carbon Composite Scaffolds

Abstract: The magnetic Fe-MBG/C composite scaffolds with enhanced mechanical strength and multifunctionality have been successfully prepared. The study showed that the Fe-MBG/C composite scaffolds with the porosity of ca. 80% had interconnected macropores (200–500 µm) and mesopores (3.7–4.4 nm) and significantly enhanced the compressive strength compared to the pure MBG scaffolds. Importantly, the Fe-MBG/C composite scaffolds exhibited good bioactivity and sustained drug release property. At the same time, the Fe-MBG/C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
10
2
Order By: Relevance
“…The magnetic parameters of 60S30C10Fe-Ar are comparable to those reported by other authors for a magnetite-containing sol-gel glass with a 45S5 basic composition [ 15 ]. Interestingly, the saturation magnetization of 60S30C10Fe-Ar is significantly higher than the value (1.32 Am 2 /kg reported for a SiO 2 -CaO-P 2 O 5 mesoporous bioactive glass (MBG) doped with 10 mol % of Fe and calcined at 700 °C in argon [ 48 ], as done in the present work. Aqueous suspensions of this Fe-doped MBG were exposed to an alternating magnetic field and it was reported that the material could effectively generate heat to raise the temperature of the surrounding environment (from 37 to 44.5 °C after 20 min) [ 48 ].…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…The magnetic parameters of 60S30C10Fe-Ar are comparable to those reported by other authors for a magnetite-containing sol-gel glass with a 45S5 basic composition [ 15 ]. Interestingly, the saturation magnetization of 60S30C10Fe-Ar is significantly higher than the value (1.32 Am 2 /kg reported for a SiO 2 -CaO-P 2 O 5 mesoporous bioactive glass (MBG) doped with 10 mol % of Fe and calcined at 700 °C in argon [ 48 ], as done in the present work. Aqueous suspensions of this Fe-doped MBG were exposed to an alternating magnetic field and it was reported that the material could effectively generate heat to raise the temperature of the surrounding environment (from 37 to 44.5 °C after 20 min) [ 48 ].…”
Section: Resultscontrasting
confidence: 68%
“…Interestingly, the saturation magnetization of 60S30C10Fe-Ar is significantly higher than the value (1.32 Am 2 /kg reported for a SiO 2 -CaO-P 2 O 5 mesoporous bioactive glass (MBG) doped with 10 mol % of Fe and calcined at 700 °C in argon [ 48 ], as done in the present work. Aqueous suspensions of this Fe-doped MBG were exposed to an alternating magnetic field and it was reported that the material could effectively generate heat to raise the temperature of the surrounding environment (from 37 to 44.5 °C after 20 min) [ 48 ]. As a direct comparison is possible between the two materials, it is expected that 60S30C10Fe-Ar may be suitable for applications in magnetic hyperthermia, too.…”
Section: Resultscontrasting
confidence: 68%
“…Interestingly, X. Li et al reported a reduction in pore size of CaO-P 2 O 5 -SiO 2 /Fe 3 O 4 glass with an increase in Ca concentrations and a decrease in Fe concentrations [11]. From the point of view of application, the biocompatibility of macro/mesoporous bioactive glasses with a magnetic phase was tested and confirmed [8-10, 12, 13]. The growth of apatites in the in vitro test is one of the common indicators of bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is observed that the apatite-forming ability and cell attachment tend to decrease with an increase in the magnetic phase in bioactive glasses [15]. In addition to bioactivity tests, the capability of the drug loading-release was also demonstrated [9, 11, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of mesoporous material in bone tissue regeneration has been proposed because of its large specific surface area and pore volume, which may improve its bioactivity and allow it to be loaded with osteogenic agents and promote new bone formation. [3][4][5] The biocompatible and bioactive mesoporous material will favor cellular growth and bone regeneration, which is very useful for building macroporous devices to be applied in bone tissue engineering. 6,7 Poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCL-PEG-PCL), a linear polyester copolymer composed of a hydrophobic PCL block and a hydrophilic PEG block, possesses good biocompatibility and suitable degradability.…”
Section: Introductionmentioning
confidence: 99%